2015
DOI: 10.1590/1980-5497201500030015
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with musculoskeletal pain among teachers: sociodemographics aspects, general health and well-being at work

Abstract: Introduction:Musculoskeletal pain is one of the most frequent complaints among teachers, compromising their health and quality of life. Objective: To estimate the prevalence of musculoskeletal pain among teachers, assessing their occurrence according to sociodemographic characteristics, general health and well-being at work. Methods: An exploratory cross-sectional study conducted with 525 teachers. During activities of continuing education, the teachers completed a self-administered questionnaire containing qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
1
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 24 publications
1
27
1
10
Order By: Relevance
“…As in other professions, ill-health among teachers may be associated with various aspects and is related to low levels of QoL. It is therefore important to gain a deeper understanding of teachers' health, exploring the biological, ergonomic, occupational, and psychosocial mechanisms underlying teaching, and to invest in practices that improve communication and interaction between workers 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…As in other professions, ill-health among teachers may be associated with various aspects and is related to low levels of QoL. It is therefore important to gain a deeper understanding of teachers' health, exploring the biological, ergonomic, occupational, and psychosocial mechanisms underlying teaching, and to invest in practices that improve communication and interaction between workers 14,15 .…”
Section: Discussionmentioning
confidence: 99%
“…Ceballos' survey has reported that the prevalence of teachers with musculoskeletal pain was over 70% [35]. Darwish argue that women often wear high-heeled shoes and this may cause fatigue and pain in lower extremities [44].…”
Section: Discussionmentioning
confidence: 99%
“…Although we have not asked the details that how long teachers stand, sit, use computers, teachers spend much time using personal computers, such as grading work, documentation, reports, contacting parents, and creating documents. It has been reported that teachers often complain of musculoskeletal pain [35]. Pain and fatigue are believed to occur from using the computer in the same or in a strained position.…”
Section: Discussionmentioning
confidence: 99%
“…Repercussions on teachers' physical and mental health and professional performance have been highlighted in different contexts, featuring the high prevalence of psychological disorders in the teaching profession 17,25 . Mental disorders are among the main causes of illness for teachers, along with musculoskeletal disorders and voice problems 13,26,27 .…”
Section: Discussionmentioning
confidence: 99%